1989
DOI: 10.1002/ijc.2910440311
|View full text |Cite
|
Sign up to set email alerts
|

Sera of children with renal tumours contain low‐molecular‐mass hyaluronic acid

Abstract: The molecular mass of hyaluronic acid (HA) rather than its serum concentration alone may be a hallmark of certain types of malignancy. A radiometric assay was used to measure HA levels in 35 children with renal tumours [33 Wilms' tumours and 2 bone metastasizing renal tumours of childhood (BMRTC)] and 20 normal siblings of children with cancer. The HA level in the sera of normal children was barely detectable and had a molecular mass of 1-5 x 10(5). In both Wilms' and BMRTC patients, very high levels of HA wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 46 publications
3
44
0
Order By: Relevance
“…Regarding the findings of Dr. Kumar's group that, although HA levels are elevated in the sera of both Wilms' tumor patients and children with bone-metastasizing renal tumor of childhood (BMRTC), HA fragments are found only in the sera of BMRTC patients, 5 our findings in cancers of the bladder, prostate and head/neck are in agreement. 6 -8 We found that HA levels are elevated in the urine of bladder cancer patients regardless of tumor grade [i.e., low (G1), intermediate (G2) and high (G3)].…”
supporting
confidence: 90%
“…Regarding the findings of Dr. Kumar's group that, although HA levels are elevated in the sera of both Wilms' tumor patients and children with bone-metastasizing renal tumor of childhood (BMRTC), HA fragments are found only in the sera of BMRTC patients, 5 our findings in cancers of the bladder, prostate and head/neck are in agreement. 6 -8 We found that HA levels are elevated in the urine of bladder cancer patients regardless of tumor grade [i.e., low (G1), intermediate (G2) and high (G3)].…”
supporting
confidence: 90%
“…5 In both Wilms' and BMRTC patients, very high levels of HA were found in preoperative serum samples; these fell markedly following surgical excision of tumours. 15 We also demonstrated the presence of low m.w. HA (similar to the angiogenic fragment of HA) in the sera of BMRTC patients.…”
mentioning
confidence: 55%
“…It has been clear for years that the HYA content of tumours is often elevated (see Ref. 30), which is consistent with the raised HYA concentrations of HYA in serum of cancer patients [31][32][33][34]. There is general agreement, however, that the HYA level in patients' sera cannot be adopted as a tool for diagnosis or prognosis though it might prove to have restricted uses for research in defined groups.…”
Section: Some General Considerationsmentioning
confidence: 73%